Moderation and the Performing Arts in Contemporary Muslim Societies - Joseph Alagha (International Institute of Islamic Thought, 2015)
Art plays an important role for politically engaged Muslims and promotes moderation (wasaṭīyah). Moderation has a civilizational mission: to buttress an open society that recognizes its inhabitants’ diversity so that they can freely and skillfully express their own cultural identity and thus contribute to enhancing the overall Islamic cultural sphere by endorsing the performing arts. The wasaṭīyah authors discussed below reject the notion of “art for art’s sake” and employ a specific genre of Islamic art commonly referred to as “purposeful art” or “art with a noble mission.” Purposeful art is “clean art” that portrays good deeds, as distinguished from bad deeds that characterize indecent or “lowbrow art.” It deals with socio-political issues as well as the themes of justice, jihad, sacrifice, and patriotism. Moderation is the norm, since “Islam is the religion of the golden mean” between excess and deficiency. From the stance of graduality, moderation affords a novel reading of the maxims of Islamic jurisprudence (qawā‘id al-fiqh), whereby the performing arts promote benefits (maṣāliḥ) and avoids harm (mafāsid).